Synthesis of Cyclodextrin-Grafted Chitosan: From Laboratory Scale to Pilot Scale - Narin Paiboon; Sarunya Phunpee; Uracha Ruktanonchai; Suvimol Surassmo; Rungthiwa Methaapanon; Treerat Vacharanukrauh; Suttichai Assabumrungrat; Apinan Soottitantawat (Organic Process Research & Development, 2023)
The CD-g-CS complex particle, made from the synthesis of toluenesulfonyl β-cyclodextrin (TsCD) and chitosan (CS), has a wide range of applications. Previous laboratory studies have proven the feasibility of the synthesis process, but larger-scale studies are necessary for wide utilization. This study aimed to scale up the reaction process from a 250 mL laboratory scale to 2, 10, and 500 L batch stirred-tank reactors, using a stepwise approach. Factors such as the mole ratio of TsCD to CS, reaction temperature, and reaction time were studied to optimize the synthesis. The degree of N-substitution (DS) was used to assess the number of grafted TsCD per primary amino group of chitosan, which is the key measure of the high-quality CD-g-CS. The results indicated that the DS increased with the increasing TsCD to CS mole ratio and reached a maximum at a reaction temperature of 95 °C. The reaction reached optimum results after 24 h. The constant heat transfer rate per unit volume was used as a successful scaling factor for the 10 and 500 L CD-g-CS processes.
Keywords: Nanocomposite Films for Food Packaging; Polymer Surface Interaction Studies; Electrospun Nanofibers in Biomedical Applications